HUBUNGAN PENDAPATAN ORANGTUA DAN POLA MAKAN SERTA KEJADIAN PENYAKIT DIARE DENGAN STATUS GIZI - Asmiati Asmiati; Rudy Hartono; Aswita Amir; Hijrah Asikin (Politeknik Kesehatan Makassar, 2017)
This type of research is analytic research using the Cross-Sectional Study approach, to obtain data on the relationship of diet and parental income and the incidence of diarrheal diseases on nutritional status (BB / TB) of the students of SDN Daya 1. Populations in this study were all elementary school students of the third, fourth, and fifth grade of SDN Daya 1 Makassar City. The sample in this study were elementary school students in the grades III, IV and V in SDN Daya 1 located in Paccerakkang village, Biringkanaya Subdistrict, Makassar City, with the following criteria: class III-V students who were willing to become a sample; children are in good health at the time of sampling; and parents and teachers are willing to become respondents. Data analysis uses the Chi-Square test. The results showed that diet was not related to nutritional status as evidenced by the value of p = 0.48 (> 0.05), parental income was not related to nutritional status where most of the parents' income level was quite sufficient as evidenced by p = 0, 269 > 0.05) as well as the incidence of diarrhea not related to nutritional status as evidenced by p = 0.470 (> 0.05). It is recommended that the process of data collection is better collaboration between researchers and the school, making direct observations at the household level regarding food availability, and adding food intake variables to find out the meal portion of the sample. Keywords: Parental Income, Diet, Diarrhea and Nutritional Status